Relationship of bitter taste perception to the PROP (6-n-propylthiouracil) taster status, and food preference and consumption of Filipino youth alcohol drinkers and nondrinkers - Lim, Riley Leroy T. (College of Home Economics, University of the Philippines Diliman, 2021)
This study aimed to assess the relationship of bitter taste perception with the PROP (6-n-propylthiouracil) taster status and food preferences and consumption of Filipino youth alcohol and non-alcohol drinkers. The respondents accomplished a food preference checklist, a 3-day food record, and were classified into nondrinkers and drinkers according to their alcohol use disorder identification test (AUDIT). Sensory evaluation of PROP/NaCl and caffeine solutions was also conducted. The respondents (n=51) were composed of 53% nondrinkers and 47% drinkers. Drinkers had a significantly (p<0.05) greater preference for beverages and foods under the bitter taste modality, as well as significantly (p<0.05) higher intake of energy and sodium than nondrinkers. The respondents were composed of 16% nontasters, 35% medium tasters, and 49% supertasters. No significant (p>0.05) correlations were found between bitter taste intensity and (a) PROP taster status, (b) drinker status, and (c) preference for the bitter taste modality. Significant (p<0.05) correlations were found between bitter taste intensity and the preference for (a) French fries (r=-0.299), (b) instant noodles (r=-0.354), (c) oatmeal (r=-0.392), (d) cauliflower (r=-0.291), (e) dried fish (r=0.286), and (f) wine (r=-0.372), and the (g) intake of calcium (r=0.297). Results of the study, in general, imply that bitter taste perception is not associated to alcohol consumption, PROP taster status, and preference for the bitter taste modality. It was shown however that it can influence the intake of calcium, and the preference for certain food items, i.e.,cauliflower and wine as supported by previous studies.